2010
DOI: 10.1089/vbz.2009.0179
|View full text |Cite
|
Sign up to set email alerts
|

Identification ofIn Vivo-Induced Conserved Sequences fromYersinia pestisDuring Experimental Plague Infection in the Rabbit

Abstract: In an effort to identify the novel virulence determinants of Yersinia pestis, we applied the gene "discovery" methodology, in vivo-induced (IVI) antigen technology, to detect genes upregulated during infection in a laboratory rabbit model for bubonic plague. After screening over 70,000 Escherichia coli clones of Y. pestis DNA expression libraries, products from 25 loci were identified as being seroreactive to reductively adsorbed, pooled immune serum. Upon sequence analysis of the predicted IVI gene products, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…It is this N terminus of the protein that is of most interest, as it is the portion that varies the most among all of the genes of the yapJ-yapK family and is the portion most likely to be engaged in interactions with the host. Based on our previous work, we know that yapJ and yapK are induced during bubonic and pneumonic infections of mice (38), and reactivity against either YapJ or YapK (and two other Yaps) has also been detected in convalescent-phase sera from experimentally infected rabbits (7), indicating that at least one of these genes is induced following subcutaneous infections of rabbits. As surface-exposed proteins expressed during infection and recognized by the adaptive immune response, these proteins of unknown function represent potential targets for new vaccines.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…It is this N terminus of the protein that is of most interest, as it is the portion that varies the most among all of the genes of the yapJ-yapK family and is the portion most likely to be engaged in interactions with the host. Based on our previous work, we know that yapJ and yapK are induced during bubonic and pneumonic infections of mice (38), and reactivity against either YapJ or YapK (and two other Yaps) has also been detected in convalescent-phase sera from experimentally infected rabbits (7), indicating that at least one of these genes is induced following subcutaneous infections of rabbits. As surface-exposed proteins expressed during infection and recognized by the adaptive immune response, these proteins of unknown function represent potential targets for new vaccines.…”
Section: Figmentioning
confidence: 99%
“…However, it was shown that the expression of yapJ and yapK is induced during mammalian infection in both bubonic and pneumonic models of plague in C57BL/6 mice (38). In addition, antibodies against YapJ were detected following experimental infection in a sublethal rabbit model of bubonic plague when the sera of surviving rabbits were screened with an Escherichia coli library expressing Y. pestis proteins (7). While expression in a host implies a role in virulence, it remained unknown what role these genes might be playing during the infectious process.…”
mentioning
confidence: 99%
“…Additional studies have since indicated that a subset of these putative autotransporter proteins possesses adhesive and autoaggregative properties (24,42,72). As more investigation has been initiated into the virulence properties of Y. pestis, some of these putative autotransporter-encoding genes have arisen in genetic screens as having potential roles in host infection or encoding immunogenic proteins (4,27,43,71) though their contributions to pathogenesis remain largely undefined.…”
mentioning
confidence: 99%
“…In analysing expression of each of the yap genes by qRT-PCR, our previous work showed that yapG expression is modestly induced during bubonic and pneumonic plague in mice (Lenz et al , 2011). Additionally, the production of YapG-specific antibodies was demonstrated during a sublethal rabbit model of bubonic plague using in vivo -induced antigen technology (Andrews et al , 2010). Based on these data, and the observation that most characterized autotransporters are either implicated in virulence or have virulence-associated functions, it seems likely that YapG also contributes to Y. pestis pathogenesis.…”
Section: Introductionmentioning
confidence: 99%